The Relationship between Academic Stress and Help-Seeking Behavior with Depression in Students - Salsabiilla, Alleidya; Candrasari, Anika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: To conduct an analysis of the relationship between academic stress and awareness in the pre-help-seeking behavior stage with the level of depression in students. Methodology: This study utilized an analytical observational study design with a cross-sectional approach. The technique used was purposive sampling and 50 respondents were obtained, and three types of questionnaires were used to measure academic stress, help-seeking behavior and depression. The data analysis methods used in the research are univariate, bivariate (Chi-Square test), and multivariate (logistic regression test). Results: According to the findings of the univariate analysis, the majority respondents were female (74.0%), moderate academic stress (52.0%), moderate help-seeking behavior (54.0%), and moderate depression (46.0%). Meanwhile, bivariate analysis found that academic stress had a significant relationship with depression levels (P=<0.001), while the awareness in the pre-help-seeking behavior stage was not related to depression levels (P=0.726). Applications/Originality/Value: To provide a new perspective on the relationship relationship between academic stress and awareness in the pre-help-seeking behavior stage with the level of depression in students.